Um amor sem fim: interações e afetos entre ouvintes de um programa romântico de rádio em Belém, no Pará - SILVA, Vanessa Monteiro da (Universidade Federal do Pará, 2021)
The objective of this research is to understand the dynamics of WhatsApp group interactions that lead to the construction of affective bonds between listeners and radio programs, based on the Amor Sem Fim radio program. The program has been broadcast since 1993 on the 99FM radio, in Belém, Pará. Amor Sem Fim proposes to pack “the hearts in love” and, more than presenting a romantic musical production, it also serves as loving mail among its listeners. Through a board called Clube da Amizade, listeners have the chance to get to know each other, and, from there, develop (or not) some kind of relationship. Throughout this duration, several couples have already graduated through the program, and Amor Sem Fim continues to play its role as cupid. Since 2014, the program has had a new way to interact with the listener: WhatsApp. Without having more space to talk live during Amor Sem Fim, the inclusion of the app as a form of participation on the radio made listeners advance in their forms of interaction, creating WhatsApp groups formed only by people who like to listen to the program. With that, they started to interact independently of the transmission time of Amor Sem Fim and the mediation by Clube da Amizade. One of these groups is Amigos do Aelson, whose interactions left the virtual field and went to the face-to-face, with listeners promoting meetings in malls, clubs, and restaurants. With this interaction, the members of the group end up establishing ties, ranging from friendships to romances. This study proposes to have a relational conception (FRANÇA, 2016; SODRÉ, 2006), having as the guiding theories the studies of interactions (LEMOS, 1997; THOMPSON, 1998, 2018; PRIMO, 2007) and the relationships of affection established between listeners (RECUERO, 2005; 2009; RUDIGER, 2013; GRISA, 2003). For this, it is necessary to understand the specifics of the radio medium, from classic studies (LOPES, 1988; BACHELARD, 2005; MCLEISH, 2001), to the present, with its new characteristics and transformations (KISCHINHEVSKY, 2007, 2016; SILVER, 2002, 2008; QUADROS, 2003, 2017). To achieve the objective of this research, the methodology adopted followed a qualitative approach, with the use of techniques such as interviews, field diary, participant observation, and documentary research. Based on the data obtained and the theory consulted, the data analysis showed that the listener presents different forms of interaction, trusts friendship with the speaker, creates affective bonds in the group and perceives the program as a bond that unites them all.